THE RELATIONSHIP BETWEEN COVID-19 SEVERITY AND THE USAGE OF ANGIOTENSIN-II RECEPTOR BLOCKERS IN HYPERTENSIVE PATIENTS (Bioresearch Communications, 2022)
Purpose of the study: As demonstrated by numerous epidemiological studies, the high incidence of hypertension among patients with coronavirus disease 2019 (COVID-2019) appears to be associated with an elevated risk of mortality. The angiotensin-converting enzyme (ACE) system is not expressed uniformly throughout the human population, and contemporary variations may account for part of the global disparities in infection prevalence. In addition, animal investigations have demonstrated that the ACE2 receptor is a potential infection route for the COVID-19-causing SARS-CoV-2 virus. As two-thirds of hypertension patients take ACE inhibitors/angiotensin receptor blockers, a number of concerns have been raised regarding the harmful or beneficial effects of contemporary antihypertensive medications in COVID-19. This study presents the most recent evidence for and against the impact of ACE blockade administration in the age of COVID-19 on the cohort of hypertension patients in Bangladesh (N = 300). Methods: We included in this study 300 patients who had a record of a COVID-19 test performed between July 2021 and September 2021 using RT-PCR. All the patients had a history of hypertension two years before the index date, based on the International Classification of Diseases codes (Tenth Revision, Clinical Modification, ICD-10-CM). All of them have been taking anti-hypertensive drugs for 1–2 years. We used logistic regression to estimate the odds ratio (OR) and the 95% confidence interval (CI) of COVID-19 severity in patients prescribed Angiotensin Receptor Blockers (ARB) versus those not prescribed ARB. We selected a cohort of 300 Bangladeshi patients who were covid posi tive and had been taking hypertensive medications for 1-5 years. Results: Among COVID-19-positive patients with hypertension, the use of ARB is associated with increased odds of hospitalization, including all patients admitted to ICU or CCU (OR = 1.008, (0.440, 2.309) and OR= 2.31, (0.024, 2.452) respectively). Participants receiving ARB have a lower odds ratio of using BiPAP, CPAP, and Ventilation (0.592, 0.010, and 0.031, respectively; p-value < 0.5) compared to the non-ARB users. Research Implications: We noticed a statistically significant association between ARB administration and mechanical ventilation in our study. Since ARB use was also related to a decreased likelihood of needing additional oxygen support, such as nasal cannula, BiPAP, and CPAP, there is sufficient evidence from other clinical factors to indicate a consistent connection between ARB use and oxygen assistance among covid-positive patients. Further research is required to determine the molecular relationship between ARB use and oxygen level in Covid-positive individuals.Bioresearch Commu. 9(1): 1180-1195, 2023 (January)